2018
DOI: 10.3390/ijms19030855
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Organic Anion Transporting Polypeptides (OATP) 1B1- and OATP1B3-Mediated Transport: An Updated Review in the Context of OATP-Mediated Drug-Drug Interactions

Abstract: Organic anion transporting polypeptides (OATP) 1B1 and OATP1B3 are important hepatic transporters that mediate the uptake of many clinically important drugs, including statins from the blood into the liver. Reduced transport function of OATP1B1 and OATP1B3 can lead to clinically relevant drug-drug interactions (DDIs). Considering the importance of OATP1B1 and OATP1B3 in hepatic drug disposition, substantial efforts have been given on evaluating OATP1B1/1B3-mediated DDIs in order to avoid unwanted adverse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 172 publications
(176 reference statements)
3
65
0
1
Order By: Relevance
“…As OATP2B1 and NTCP are localized to two different chromosomes (11 and 14, respectively), the possibility of common regulatory mechanisms related to trans‐acting factors that interact with DNA–protein binding domains or posttranscriptional regulation of messenger RNA stability by binding to an element on the RNA molecule should be considered. Although candidate factors have been suggested, ( 15,35,36 ) further investigation will be required to elucidate the importance of these potential regulatory mechanistic components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As OATP2B1 and NTCP are localized to two different chromosomes (11 and 14, respectively), the possibility of common regulatory mechanisms related to trans‐acting factors that interact with DNA–protein binding domains or posttranscriptional regulation of messenger RNA stability by binding to an element on the RNA molecule should be considered. Although candidate factors have been suggested, ( 15,35,36 ) further investigation will be required to elucidate the importance of these potential regulatory mechanistic components.…”
Section: Discussionmentioning
confidence: 99%
“…4D), they could result in reduced uptake of their ligands, adding to effects produced by vascular shunting around the liver from portal hypertension as well as loss of sinusoidal endothelial fenestrations, reducing access of protein‐bound ligands to the space of Disse and hepatocyte basolateral plasma membrane transporters. ( 3,37 ) It should also be noted that most individuals from whom tissue was obtained were on various medications that could potentially increase or decrease transporter expression, ( 36,38 ) although such effects have not been well characterized in human liver. Our results also differ from those reported using mass spectroscopic analysis in which there was no difference in OATP1B1 expression in cirrhosis while expression of OATP1B3 was reduced and expression of OATP2B1 was increased ( 39 ) ; we found that neither was changed.…”
Section: Discussionmentioning
confidence: 99%
“…Known substrates of OATP1B1 and OATP1B3 include statins, repaglinide, olmesartan, enalapril, valsartan, several xenobiotic glucuronide metabolites, as well as a host of cytotoxic chemotherapeutic agents, including the taxanes paclitaxel and docetaxel, the platinum-based drug cisplatin, and methotrexate. As hypertension and diabetes are among the prevalent comorbidities in cancer patients, many xenobiotic OATP1B1 and OATP1B3 substrate drugs are likely to be co-administrated with OATP-inhibitory TKIs, and therefore, clinically significant toxicities such as rhabdomyolysis, hyperkalemia, and hypoglycemia can be anticipated [ 39 , 40 , 41 ].…”
Section: Organic Anion Transporting Polypeptides (Oatps)mentioning
confidence: 99%
“…Our previous findings on the role of the OATP-KAT pathway in rickettsial pathogen-tick interactions [ 12 ] and the present findings on their roles in LGTV-tick interactions suggest that these conserved molecules play central roles in vector-pathogen interactions. Post-translational modifications are critical for OATPs to function efficiently [ 33 35 ]. Therefore, understanding putative post-translational modification sites on OATPs is highly required.…”
Section: Resultsmentioning
confidence: 99%